2022
DOI: 10.1155/2022/3188710
|View full text |Cite|
|
Sign up to set email alerts
|

The Technique of Phacoemulsification and Intraocular Lens Implantation in Subluxated Cataract Surgery

Abstract: The purpose of this study was to investigate the effectiveness and practicability of phacoemulsification and intraocular lens implantation for subluxated cataracts. A retrospective review of subluxated cataract surgeries of 19 eyes performed in Kunhua Hospital Affiliated with Kunming University of Science and Technology between January 2017 and June 2021 was conducted. We choose to use the rotate-and-chop phacoemulsification techniques described when the crystal nucleus is rotated out of the capsular bag and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…DISCUSSION Cataract surgery is difficult in traumatic eyes with zonular insufficiency or subluxation of the lens. Previously, intracapsular cataract extraction (ICCE) was necessary for patients with zonular dialysis [8] . The capsular bag could not be saved in most cases.…”
Section: Resultsmentioning
confidence: 99%
“…DISCUSSION Cataract surgery is difficult in traumatic eyes with zonular insufficiency or subluxation of the lens. Previously, intracapsular cataract extraction (ICCE) was necessary for patients with zonular dialysis [8] . The capsular bag could not be saved in most cases.…”
Section: Resultsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%